Estimativa da evapotranspiração da cultura do Tagetes patula pelo método da razão de Bowen, em ambiente protegido e a campo - Boueri, Millena Ariana [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
The objective of this work was to apply the energy balance method partition of the available solar energy, in the processes of evaporation (latent heat), heating of air and the plants (sensible heat) and in the heating of the ground (flux of heat in the ground), in the Tagetes patula crop, inside and outside a greenhouse; and to compare the values of crop evapotranspiration (ETc) measured in water table lysimeters, with that estimated by the energy balance method, in two environments. The experiment was carried on the experimental area of the Department of Natural Resources - Section Environmental Sciences of the College of Agricultural Sciences, UNESP, Botucatu-SP, in the period from 21/05 to 09/08/02. The experimental area was constituted of two areas of 280m2, being one at field conditions and the other in greenhouse arch type, with covering of polyethylene of low density (HDPE), light spreading, with 150ìm of thickness, and polypropylene screen with 50% reduction of the solar radiation in the laterals. The results showed that the net radiation was distributed in 102% for LE, 2% for H and 9% for G inside a greenhouse. In the field condition, the distribution was of 95%, 14% and 13% for LE, H and G, respectively. The values of LE/Rn above of 100% must it the advection effect, having lateral transport of energy of the neighboring area for the culture, representing additional source of energy (lateral profit) for the evapotranspiration. Although the constructive characteristics of the water table lysimeters sheet allow that the superficial irrigations can be excused, in these conditions not the evaporation of the ground or the slowness in the hair ascension for interruption of the capillarity in the first centimeters of ground, more transpiration occurs. The evapotranspiration for the Bowen ratio method, presented average values of 50 and 55% greaters to the measured ones for the lysimeters... (Complete abstract click electronic access below)
Keywords: Evapotranspiração; Estufas; Flores - Cultivo; Tagetes; Balanço de energia; Evapotranspiration